Effect of patient position on measurement of patellar height ratio - Rapeepat Narkbunnam (2018)
© 2015, Springer-Verlag Berlin Heidelberg. Background: Patient position is an important factor which can affect the accuracy of patellar height ratio measurement. Varying degree of knee flexion angles and action of quadriceps muscle while supine or standing positions are the most concerning factors. Methods: Forty healthy subjects had radiographs taken of their knees at 0°, 30°, and 60° of flexion in the supine (non-weight-bearing) and standing (weight-bearing) positions. Patellar height was assessed by five different measurement methods including Insall-Salvati (IS), Modified Insall-Salvati (MIS), Caton-Deschamps (CD), Blackburne-Peel (BP), and Knee triangular ratio (KT). Results: The mean and standard deviation (SD) in the supine/standing position of each method were IS 1.0 (0.1)/1.05 (0.1), MIS 1.6 (0.2)/1.8 (0.3), CD 1.0 (0.2)/1.2 (0.2), BP 0.9 (0.2)/1.0(0.2), and KT 1(0.1)/1(0.1). Significant differences were found between supine and standing positions using all of the methods except for KT ratio. Comparisons between the various knee flexion angles were found to be statistically significant by most of the measurement methods, although the differences between the means were less than their SD. Conclusion: Quadriceps action had a significant influence on the mean values obtained by the MIS, CD, and BP methods. In clinical practice, interpretation for patella alta or patella baja of these measurement methods should be normalized according to the patient position. Varying the degree of knee flexion did not produce clinically important effects in any of the five patellar height measurement methods.